Analisis Pengembangan Ektrakulikuler Terhadap Minat Bakat Peserta Didik Di Sekolah Dasar (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Extracurricular is an educational process devoted to training and developing students' talents and interests beyond their academic abilities which is carried out outside of school intracurricular activities. This study used descriptive qualitative method. With data collection techniques in the form of interviews, observation, library research and documentation. The aim of this research is to analyze extracurricular development of elementary school students' talents and interests.